The effects of the interactions between monetary and fiscal policy on the Euro Area’s GDP: An ARDL approach - Almeida, Ana Marta Gonçalves Peres de (2021)
This Dissertation provides an empirical analysis regarding the effects of the interactions between monetary and fiscal policies in the Euro Area’s GDP, using quarterly data from 2000 until 2020. Using an ARDL-EC model to analyse the long run and short run effects on the Euro Area’s GDP, the equation includes monetary policy variables, fiscal policy variables, and a proxy for its interactions. This Dissertation concludes that the Euro Area’s GDP is positively impacted by monetary policy in the long run and short run, while the impact of fiscal policy is negative. The result for the interactions between monetary and fiscal policy is encouraging for further research on this topic, because of the model’s quick adjustment speed and the favourable evolution of the proxy for the policy mix, in the analysis of its economic significance through the different business cycles.